Comparison of vitrification and slow freezing for cryopreservation of cleavage stage embryos (Day 3) and its impact on clinical outcome - Choudhary, Manisha; Soni, Ravikant; Swarankar, Mohan Lal; Garg, Swati (International Journal of Research in Medical Sciences, 2017)
Background: The objective of this retrospective study was to compare the efficacy of slow freezing and Vitrification for the cryopreservation of supernumerary cleavage stage embryos on day 3 after IVF and its impact on clinical outcome. Methods: 485 supernumerary embryos of IVF cycles (from Oct 2011 to Dec 2012) were cryopreserved by slow freezing method while 502 embryos (from Jan 2013 to April 2014) by Vitrification method. 362/485 and 230/502 embryos were thawed for FET cycles (65 patients in each group).After warming the survival rate, post warmed embryo morphology, clinical pregnancy and implantation rates were evaluated and compared between the two groups. Results: There were 65 frozen thawed cycles in each group. The percentage of excellent and good morphology embryos before cryopreservation were same in both the groups, but after thawing the results were significantly in favour of Vitrification as compared to Slow freezing. In Vitrification group versus Slow freezing group, the different outcomes were survival rate (96.95% vs. 69.06%, p-0.000), post warmed excellent morphology embryos (94.17% vs. 60.8%, p-0.000) clinical pregnancy rate (41.53% vs. 21.53%, p-0.043) and the implantation rate (14.41% vs. 7.01%, p-0.024). Conclusions: Vitrification is a promising alternate to the conventional slow freezing method in terms of not only excellent survival and post warmed excellent morphology embryo rate but also higher clinical pregnancy and implantation rate.